1987
DOI: 10.1007/bf00187252
|View full text |Cite
|
Sign up to set email alerts
|

Effects of amphetamine, methylphenidate, and apomorphine on regional brain serotonin and 5-hydroxyindole acetic acid

Abstract: Electrophysiological and cytofluorometric data suggest that doses of amphetamine which enhance locomotor activity and promote focused stereotypies produce pronounced effects on serotonin pathways in the CNS. However, the biochemical evidence regarding changes in serotonergic function produced by moderate doses of this drug is inconsistent. Therefore, the present study was designed to further examine the effects of amphetamine (1-5 mg/kg) on regional brain serotonin and its metabolite and to compare these effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…5B). Similar effects of amphetamine (13,60) and methylphenidate (59, 65) on c-Fos expression (59,60) and neurochemical indices of serotonergic transmission (13,65) in the frontal cortex of rats have been reported. The present data suggest that one of the potential mechanisms of psychostimulant action to affect glutamatergic transmission, and, consequently, dopaminergic hyperactivity, may involve modulation of 5-HT transmission in the frontal cortex.…”
Section: Psychostimulants Modulate Serotonergic Transmission In the Fsupporting
confidence: 61%
“…5B). Similar effects of amphetamine (13,60) and methylphenidate (59, 65) on c-Fos expression (59,60) and neurochemical indices of serotonergic transmission (13,65) in the frontal cortex of rats have been reported. The present data suggest that one of the potential mechanisms of psychostimulant action to affect glutamatergic transmission, and, consequently, dopaminergic hyperactivity, may involve modulation of 5-HT transmission in the frontal cortex.…”
Section: Psychostimulants Modulate Serotonergic Transmission In the Fsupporting
confidence: 61%
“…The reason for this may lie in the proximal effect of the two drugs. Whilst the proximal effects of both MPH and d-amphetamine are mediated by DA and NA (Easton et al, 2007;Kuczenski & Segal, 1997), d-amphetamine also has significant effects on 5-HT (Holmes & Rutledge, 1976) at higher doses (Kuczenski & Segal, 1989), whereas the effect of MPH on 5-HT is less clear Kuczenski & Segal, 1997;Kuczenski et al, 1987). Amphetamine's stronger effects on 5-HT mediated transmission, which is uniformly depressant in the SC (Kawai & Yamamoto, 1969;Straschill & Perwein, 1971), may be sufficient to combat and overcome any facilitatory effects stemming from cortical activation.…”
Section: Overall Discussionmentioning
confidence: 99%
“…The proximal effects of MPH are mediated by increasing synaptic levels of the monoamines dopamine (DA) and noradrenaline (NA; Kuczenski & Segal, 1997;Easton et al, 2007) and possibly serotonin (5-HT; Kuczenski et al, 1987). Evidence suggests SC itself receives extensive noradrenergic (Lindvall & Bjorklund, 1974;Weller et al, 1987) and serotonergic (Parent et al, 1981;Weller et al, 1987) innervation, as well as a limited dopaminergic input (Weller et al, 1987;Campbell et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…For example Winstanley et al (2003) have found that effects of amphetamine, which also increases 5-HT transmission (Kuczenski et al, 1987), on intertemporal choice are attenuated by 5-HT depletion. One implication of this observation is that (some of) the calming, anti-impulsive effects of amphetamine administration in ADHD might be related to the drugs' enhancing effect on 5-HT transmission.…”
Section: Intertemporal Choicementioning
confidence: 99%